Math, asked by lalnunhlui78, 2 months ago

Prove that
1+cot theta/sin theta + 1+tan theta/cos theta = cosec theta sec² theta+sec theta cosec² theta

(using LHS/RHS method)



Spam=Report Have a nice day ahead y'all!​

Attachments:

Answers

Answered by mathdude500
5

\large\underline{\sf{To\:prove - }}

 \sf \: \dfrac{1 + cot\theta}{sin\theta}  + \dfrac{1 + tan\theta}{cos\theta}  = cosec\theta \:  {sec}^{2}\theta + sec\theta {cosec}^{2}\theta

 \green{\large\underline{\sf{Solution-}}}

Consider, LHS

\rm :\longmapsto\: \dfrac{1 + cot\theta}{sin\theta}  + \dfrac{1 + tan\theta}{cos\theta}

We know,

\boxed{ \tt{ \: cotx =  \frac{cosx}{sinx} \:  \: and \:  \: tanx =  \frac{sinx}{cosx} \: }}

So, on substituting these Identities, we get

\rm \:  =  \:\dfrac{1 + \dfrac{cos\theta}{sin\theta} }{sin\theta}  + \dfrac{1 + \dfrac{sin\theta}{cos\theta} }{cos\theta}

\rm \:  =  \:\dfrac{\dfrac{sin\theta + cos\theta}{sin\theta} }{sin\theta}  + \dfrac{ \dfrac{cos\theta + sin\theta}{cos\theta} }{cos\theta}

\rm \:  =  \:\dfrac{sin\theta + cos\theta}{ {sin}^{2}\theta }  + \dfrac{sin\theta + cos\theta}{ {cos}^{2} \theta}

\rm \:  =  \:(sin\theta + cos\theta)\bigg[\dfrac{1}{ {sin}^{2} \theta} + \dfrac{1}{ {cos}^{2} \theta}  \bigg]

\rm \:  =  \:(sin\theta + cos\theta)\bigg[\dfrac{ {cos}^{2} \theta +  {sin}^{2} \theta}{ {sin}^{2} \theta {cos}^{2}\theta } \bigg]

We know,

\rm :\longmapsto\:\boxed{ \tt{ \:  {sin}^{2}x +  {cos}^{2}x = 1 \: }}

So, using this identity, we get

\rm \:  =  \:(sin\theta + cos\theta)\bigg[\dfrac{1}{ {sin}^{2} \theta \:  {cos}^{2}\theta} \bigg]

\rm \:  =  \:\dfrac{sin\theta + cos\theta}{ {sin}^{2} \theta  {cos}^{2} \theta}

\rm \:  =  \:\dfrac{sin\theta }{ {sin}^{2} \theta  {cos}^{2} \theta}  + \dfrac{cos\theta }{ {sin}^{2} \theta  {cos}^{2} \theta}

\rm \:  =  \:\dfrac{1}{sin\theta {cos}^{2} \theta}  + \dfrac{1}{cos\theta {sin}^{2} \theta}

We know,

\boxed{ \tt{ \:  \frac{1}{sinx} = cosecx \:  \:  \: and \:  \:  \:  \frac{1}{cosx} = secx \: }}

So, using this, we get

\rm \:  =  \:cosec\theta {sec}^{2}\theta + sec\theta {cosec}^{2}\theta

Hence,

\red{ \boxed{\sf \: \dfrac{1 + cot\theta}{sin\theta}  + \dfrac{1 + tan\theta}{cos\theta}  = cosec\theta \:  {sec}^{2}\theta + sec\theta {cosec}^{2}\theta}}

Additional Information:-

Relationship between sides and T ratios

sin θ = Opposite Side/Hypotenuse

cos θ = Adjacent Side/Hypotenuse

tan θ = Opposite Side/Adjacent Side

sec θ = Hypotenuse/Adjacent Side

cosec θ = Hypotenuse/Opposite Side

cot θ = Adjacent Side/Opposite Side

Reciprocal Identities

cosec θ = 1/sin θ

sec θ = 1/cos θ

cot θ = 1/tan θ

sin θ = 1/cosec θ

cos θ = 1/sec θ

tan θ = 1/cot θ

Co-function Identities

sin (90°−x) = cos x

cos (90°−x) = sin x

tan (90°−x) = cot x

cot (90°−x) = tan x

sec (90°−x) = cosec x

cosec (90°−x) = sec x

Fundamental Trigonometric Identities

sin²θ + cos²θ = 1

sec²θ - tan²θ = 1

cosec²θ - cot²θ = 1

Similar questions